2009
DOI: 10.1016/j.iheduc.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the use of technology to foster peace via Adventure Learning

Abstract: In this paper we present and discuss the findings of a systematic literature review on the use of educational technology initiatives to foster peace outcomes, and we relate those findings to Adventure Learning. In the first section of the paper, we suggest that technology-infused peace initiatives rely predominantly on targeting antecedents to peace, such as collaboration, interaction, communication, and understanding of the "other", rather than peace itself, while at the same time employing varied pedagogies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A further meta-review of the participants' contribution across both scenarios (peace and immigrations) offered three larger dimensions in this arena. These themes and dimensions enrich the results of the recent systematic review by 12 Andri Ioannou et al Veletsianos and Eliadou (2009), which only emphasized the use of technology for educational tasks (learning activities) relevant to peace. More importantly, these themes and dimensions provide insights pertinent to future research in the HCI and learning communities concerning the use of technology for peace.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…A further meta-review of the participants' contribution across both scenarios (peace and immigrations) offered three larger dimensions in this arena. These themes and dimensions enrich the results of the recent systematic review by 12 Andri Ioannou et al Veletsianos and Eliadou (2009), which only emphasized the use of technology for educational tasks (learning activities) relevant to peace. More importantly, these themes and dimensions provide insights pertinent to future research in the HCI and learning communities concerning the use of technology for peace.…”
Section: Discussionsupporting
confidence: 57%
“…The most recent systematic review on the use of technology to promote peace and humanitarianism was conducted by Veletsianos and Eliadou (2009). The review revealed that a few (educational) technologies have been used in interventions associated with the promotions of peace such as: (i) learning management systems and virtual learning environments to host learning activities, (ii) Web 2.0 technologies (blogs, wikis, social networking sites and video sharing sites) as well as email and video conferencing to promote collaboration communication, diversity and international cooperation between conflicting parties and (iii) online and video (serious) games and MMORPGs to promote exposure to diverse populations and collaborative learning through social interaction (e.g.…”
Section: Technology For Peacementioning
confidence: 99%
See 2 more Smart Citations
“…ISIS was unique but it was far from the only example of such cross-cultural educational initiatives. Many similar projects and entities, with names like ePals, iEARN (Gragert 2012 ), Seeds of Empowerment (Buckner and Kim 2012 ; Kim 2009 ), the World Forum (Bonk and Sugar 1998 ), World Savvy, Taking It Global, RoundSquare, Adventure Learning (Miller et al 2008 ; Veletsianos and Eliadou 2009 ), Learning Circles (Riel 1993 ) and Soliya, have been developed since the 1980s. Millions of learners around the world have participated in them and continue to do so.…”
Section: Some Stories To Be Toldmentioning
confidence: 99%